Design of Web-Based Attendance Application Information System at SDN Walantaka 3 - Karpan, Ibnu; Maulana, Muhamad Riyan (Yayasan Insan Mulia Bima, 2024)
Advances in information technology have resulted in significant transformations in various sectors, including in improving the efficiency and accuracy of data management in educational institutions. SDN Walantaka 3 still uses a manual attendance system, which often faces efficiency and accuracy problems in managing teacher attendance. This research aims to develop a web-based attendance application to overcome the limitations of the manual system and facilitate the management of attendance data. The method used in this research uses the waterfall software development model. The indicators used include the development process, system validation, application feasibility, and evaluation of its effectiveness. The developed system includes various features, including a login page, an intuitive dashboard, teacher master data, and an integrated attendance module. Testing of the application showed positive results, with the system successfully improving efficiency, accuracy, and minimising the potential for human error in recording attendance. The app also provides real-time access to attendance data, allowing the school to conduct better and more structured monitoring and reporting. Overall, the implementation of this application improves the effectiveness of attendance management at SDN Walantaka 3 and provides a sustainable solution for school administration needs.